Process of designing instruments for teaching performance evaluation: experience in a distance education unit of higher education - Ávila, Karla (2020)
The main objective of this study was the design and implementation of instruments to evaluate teacher’s performance in a higher education distance unit of a public mexican university. The process consisted of an eight-stage program, based on information generated by interviews, group discussions and document revisions. As a result, three instruments were designed and implemented to collect information from different perspectives: from the student, the supervisor and the evaluated person himself.